ANALISA STRATA PENDIDIKAN TERHADAP KUALITAS HIDUP MASYARAKAT - Roniyanto Roniyanto; Arif Hidayat; Linawati Mawardi (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2023)
Current conditions, including quality of life, lived or faced by an individual or society are influenced by many factors, one of which is the choice in determining the strata or level of education. Quality of life itself is an individual's subjective perspective related to the position and condition he lives, which contains elements of values, culture, religion, expectations, and social systems. This paper seeks to determine the strata of education in relation to the quality of life of the Guardians of Mutiara Bantul Kindergarten, Yogyakarta. The research was conducted using a field approach with quantitative methods. The sampling technique used accidental sampling of 84 respondents. The measurement technique uses the Linkert scale. The results of regression analysis showed that there was a significant and positive relationship between perceptions, interests, and decisions to attend higher school on quality of life. The higher the perceptions, interests, and decisions to attend higher school in a particular educational strata, the higher the level of quality of life. This is in line with the creation of conditions in building one's quality of life with growth becoming through increasing knowledge and skills.